Nanoparticle‐Structured Highly Sensitive and Anisotropic Gauge Sensors. Issue 35 (2nd June 2015) - Zhao, Wei; Luo, Jin; Shan, Shiyao; Lombardi, Jack P.; Xu, Yvonne; Cartwright, Kelly; Lu, Susan; Poliks, Mark; Zhong, Chuan‐Jian
<x xml:space="preserve">Abstract</x> The ability to tune gauge factors in terms of magnitude and orientation is important for wearable and conformal electronics. Herein, a sensor device is described which is fabricated by assembling and printing molecularly linked thin films of gold nanoparticles on flexible microelectrodes with unusually high and anisotropic gauge factors. A sharp difference in gauge factors up to two to three orders of magnitude between bending perpendicular (B⊥) and parallel (B||) to the current flow directions is observed. The origin of the unusual high and anisotropic gauge factors is analyzed in terms of nanoparticle size, interparticle spacing, interparticle structure, and other parameters, and by considering the theoretical aspects of electron conduction mechanism and percolation pathway. A critical range of resistivity where a very small change in strain and the strain orientation is identified to impact the percolation pathway in a significant way, leading to the high and anisotropic gauge factors. The gauge anisotropy stems from molecular and nanoscale fine tuning of interparticle properties of molecularly linked nanoparticle assembly on flexible microelectrodes, which has important implication for the design of gauge sensors for highly sensitive detection of deformation in complex sensing environment or on complex curved surfaces such as wearable electronics and skin sensors.